Evolution of the initiating enzymes of the complement system - Nonaka, Masaru (BioMed Central, 2002)
Analysis of the human MASP-1/3 gene, which encodes two proteases of the lectin-triggered complement cascade, has revealed alternatively used serine-protease-encoding regions for the gene's two protein products. Phylogenetic studies indicate that one arose by retrotransposition early in vertebrate evolution, supporting the idea that the lectin branch of the complement cascade arose earlier than the 'classical' pathway.